Tree Cover Mediates the Effect of Artificial Light on Urban Bats - Straka, Tanja M.; Wolf, Maritta; Gras, Pierre; Buchholz, Sascha; Voigt, Christian C. (Frontiers in Ecology and Evolution, 2019)
With urban areas growing worldwide, so does artificial light at night (ALAN) which negatively affects many nocturnal animals, including bats. The response of bats to ALAN ranges from some opportunistic species taking advantage of insect aggregations around street lamps, particularly those emitting ultraviolet (UV) light, to others avoiding lit areas at all. Tree cover has been suggested to mitigate the negative effects of ALAN on bats by shielding areas against light scatter. Here, we investigated the effect of tree cover on the relationship between ALAN and bats in Berlin, Germany. In particular, we asked if this interaction varies with the UV light spectrum of street lamps and also across urban bat species. We expected trees next to street lamps to block ALAN, making the adjacent habitat more suitable for all species, irrespective of the wavelength spectrum of the light source. Additionally, we expected UV emitting lights next to trees to attract insects and thus, opportunistic bats. In summer 2017, we recorded bat activity at 22 green open spaces in Berlin using automated ultrasonic detectors. We analyzed bat activity patterns and landscape variables (number of street lamps with and without UV light emission, an estimate of light pollution and tree cover density around each recording site within different spatial scales) using generalized linear mixed-effects models with a negative binomial distribution. We found a species-specific response of bats to street lamps with and without UV light, providing a more detailed picture of ALAN impacts than simply total light radiance. Moreover, we found that dense tree cover dampened the negative effect of street lamps without UV for open-space foraging bats of the genera Nyctalus, Eptesicus and Vespertilio, yet it amplified the already existing negative or positive effect of street lamps with or without UV on Pipistrellus pipistrellus, P. pygmaeus and Myotis spp.. Our study underpins the importance of minimizing artificial light at night close to vegetation, particularly for bats adapted to spatial complexity in the environment (i.e. clutter-adapted species), and to increase dense vegetation in urban landscape to provide, besides roosting opportunities, protection against ALAN for open-space foraging bats in city landscapes.